Estudo Químico-Biológico de Pyrostegia venusta (Ker Gawl.) Miers (Bignoniaceae) - Altoé, Thales Del Puppo (2014)
This paper describes the chemical and biological investigation of the crude extract and the hexane and ethyl acetate partitions, of the leaves of Pyrostegia venusta (Ker Gawl.) Miers, popularly known as "cipó de São João". Pyrostegia venusta is classified botanically as a median size vine, having a characteristically exuberant red flowering and so, being used as an ornamental plant. This plant has a wide use in folk medicine, being used in the treatment of vitiligo, diarrhea, bronchitis, flu, icterus and infections. The objectives of this work were to identify the classes of secondary metabolites present, identify secondary metabolites of this species, evaluate the antioxidant potential of samples of P. venusta (crude extract, ethyl acetate and hexane fractions), to quantify the amount of flavonoids in the crude extract, verify safety use of this plant in terms of cell viability (CV) front of murine macrophages (RAW 264.7) (immuno assay). Additionally, the viability results were compared with four commercial anti-inflammatory compounds (acetylsalicylic acid, indometacin, piroxicam and betamethasone), and test crude extracts for inhibition of cathepsins K and V. The identification tests confirmed the presence of flavonoids, coumarins and steroids in the samples. The chromatographic method associated to mass spectrometry analysis, led to the identification of compounds: phytol (1), sitosterol (2), stigmasterol (3) and campesterol (4). The crude extract had inhibitory activity against both tested cathepsins (K e V). The ethyl acetate fraction showed the highest antioxidant activity in the methodologies of DPPH inhibition (IC50 38.62 mg/mL) and ABTS radical (IC50 27.58 mg/mL). The total flavonoids content in the crude extract was 148.5 ± 7.65 mg / mg (14.85% (w/w)), which explains the observed antioxidant activity, since these have antioxidant activity. Samples of P. venusta had CV values greater than the commercial anti-inflammatory, which showed CV below the negative control, as well as the crude extract and the ethyl acetate fraction, the hexane fraction obtained values above the negative control, being these larger VC results between samples of P. venusta.